Impact of Farmforestry on Socio-Economic Condition of Farming Communities in District Mardan, Pakistan - Kamran Khan; Sami Ullah; Asad Ullah; Salman Khan; M. Yoserizal Saragih (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The present study was carried out to find out the socio-economic impacts of farm forestry on tree farmers in district Mardan. Survey was conducted in four villages and the farmers were asked directly at their farms through a well structure questionnaire. Most of the respondents were literate with large family size. Average farm size was found to be 9.43 acres. 15% of the respondents were self-cultivator while 85% were tenant. In the study area 13700 trees of different species have been planted on an average of 249 trees per farm. 66% farmers were interested to plant more trees on their farm in future, while 34% were found uninterested. It was noted that 7015 tress were sold at an average of 127 trees per farm during last five years and Rs 1903000 were earned from sale of trees. Fifty eight percent of the respondents were found agree and 23% disagree when they were asked whether they were socio-economically uplifted or not. 76% of respondents grow trees for sale and remaining 24% grow trees for domestic purpose. 11% of respondents purchased fuel wood during the last 10 years and the remaining 89% did not.  14% of the respondents purchased timber during last ten years while 86% did not. Those respondents who were found agree earned two types more income.